Kesenjangan Gender di Dunia Kerja Berdasarkan Perspektif Hukum - Zalkia Salsabila; Aliya Perawita; Sudirman Sitepu; Dwi Putri Lestarika (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2024)
The gender gap refers to significant differences between men and women in opportunities to participate in, among other things, employment. The gender gap in the world of work is a complex and relevant issue in the legal context. Although there is a legal framework that supports gender equality, its implementation is still hampered by patriarchal culture, systemic discrimination, and low legal awareness among workers. This gap is often caused by social and cultural norms that shape gender roles, where women often experience discrimination and injustice. This research aims to analyze the concept of gender gap in a legal perspective, by referring to various theories and related laws. Through a qualitative method with desk study, literature review and case analysis, this research will identify common forms of gender inequality in the workplace, such as wage disparity, discrimination in promotion, and inequality in access to employment opportunities.